RELATIONSHIP BETWEEN COMMUNICATION OF NURSES AND PATIENTS’ SATISFACTION WITH MECHANICAL VENTILATORS IN THE ICU - Nancy, Marsha Yoke; Artanti Nisman, Wenny; Setiyarini, Sri Setiyarini (Jurnal Manajemen Kesehatan Indonesia, 2025)
Communication between nurses and patients is one of the keys to the success of health services in hospitals. Patients who are treated in the ICU and using mechanical ventilators need to communicate with nurses and other health workers. However, they have difficulties in communication, which can have an impact on their satisfaction. To find out the relationship between communication of nurses and satisfaction of patients with ventilators in the ICU. This was a quantitative research with a cross-sectional design. The sampling technique used was consecutive sampling with forty three patient respondents who had been discharged from the ICU. The research used patient satisfaction and Nurse Quality of Communication with Patient (NQCPQ) questionnaires as the instruments. The data in this research was analyzed by using pearson correlation. According to the assessment, communication of nurse in the ICU was in the good category by 81.4%, while satisfaction of patient satisfaction with the nursing services in the ICU was in the satisfied category by 55.8%. In addition, based on the results of the Pearson analysis, p-value was 0.013 and (r) was 0.378. There was a positive relationship between communication of nurses and patients with mechanical ventilators in the ICU.